Synergistic cardioprotective effects of melatonin and deferoxamine through the improvement of ferritinophagy in doxorubicin-induced acute cardiotoxicity - Hanna, Mira; Seddiek, Hanan; Aboulhoda, Basma Emad; Morcos, George N. B.; Akabawy, Ahmed M. A.; Elbaset, Marawan Abd; Ibrahim, Abdelsatar Abdelsatar; Khalifa, Mohamed Mansour; Khalifah, Ibtesam Mahmoud; Fadel, Mostafa Said; Shoukry, Tarek (Frontiers in Physiology, 2022)
Ferritinophagy is one of the most recent molecular mechanisms affecting cardiac function. In addition, it is one of the pathways by which doxorubicin, one of the anticancer drugs commonly used, negatively impacts the cardiac muscle, leading to cardiac function impairment. This side effect limits the use of doxorubicin. Iron chelators play an important role in hindering ferritinophagy. Antioxidants can also impact ferritinophagy by improving oxidative stress. In this study, it was assumed that the antioxidant function of melatonin could promote the action of deferoxamine, an iron chelator, at the level of ferritinophagy. A total of 42 male Wistar rats (150–200 g) were divided into seven groups (n = 6) which consisted of group I: control normal, group II: doxorubicin (Dox), group III: melatonin (Mel), group IV: deferoxamine (Des), group V: Mel + Dox, group VI: Des + Dox, and group VII: Mel + Des + Dox. Groups III, V and VII were orally pretreated with melatonin 20 mg/kg/day for 7 days. Groups IV, VI and VII were treated with deferoxamine at a 250 mg/kg/dose once on D4 before Dox was given. Doxorubicin was given at a 20 mg/kg ip single dose. On the 8th day, the rats were lightly anaesthetized for electrocardiography analysis and echocardiography. Serum samples were collected and then sacrificed for tissue sampling. The following biochemical assessments were carried out: PCR of NCOA4, IREB2, FTH1, SLC7A11, and GPX4; and ELISA for serum cTnI, serum transferrin, tissue GSH, and malondialdehyde. In addition, histopathological assessment of heart injury; immunostaining of caspase-3, Bax, and Bcl2; and physiological function assessment by ECG and ECHO were carried out. Doxorubicin-induced acute significant cardiac injury with increased ferritinophagy and apoptosis responded to single and combined prophylactic treatment, in which the combined treatment showed mostly the best results. In conclusion, using melatonin as an antioxidant with an iron chelator, deferoxamine, could hinder the hazardous cardiotoxic effect of doxorubicin. However, further studies are needed to detect the impact of higher doses of melatonin and deferoxamine with a prolonged treatment period.